Speech at the University Merit Recognition Ceremony - Echeverría Andrade, Bolívar (2025)
This address was delivered at the Ceremony of Recognition for University Merit awarded to Bolívar Echeverría at the UNAM. This version of the text was dated by the author on June 15, 2009, and appeared on the website Bolívar Echeverría: Discurso Crítico y Filosofía de la Cultura (www.bolivare.unam.mx) under a Creative Commons 2.5 license. We reproduce this address with permission from Archivo Bolívar Echeverría.